Effect of interlayer dwell time on output quality in wire arc additive manufacturing of low carbon low alloy steel components - Turgut, Batuhan; Gurol, Ugur; Onler, Recep (Springer London Ltd, 2023)
Wire arc additive manufacturing (WAAM) has gained significant attention over the past decade due to its advantages, such as high productivity, cost-effectiveness, and ease of application. However, predictable WAAM of components with designed properties is still challenging due to the lack of comprehensive understanding of the process that uses considerable heat input. The interlayer dwell time is a critical process parameter in WAAM that impacts the thermal history of the manufacturing part, thereby controlling the output quality. This experimental study investigates the effect of interlayer dwell time on the microstructure and mechanical properties of low carbon low alloy steel components fabricated by WAAM. Three samples were produced by WAAM using identical process conditions by employing continuous deposition, 60 s, and 120 s dwelling after each layer deposition, respectively. The temperature profiles on both the substrate and the interlayer, hardness, yield strength, and microstructure variation were comparatively investigated. It was shown that the interlayer dwell time can significantly allow controlling the temperature fields experienced in the part, in turn, both mechanical and microstructural properties are modified. In addition, since the distance to the substrate increases with increasing built height, the thermal history and local properties of the specimens were found to be affected. Thus, a constant interlayer dwell time does not provide identical interlayer temperatures. It was found that compared to the samples without interlayer dwell time the samples with 120 s dwell time showed around 18% and 10% increased average hardness and average yield strength, respectively.
Keywords: Additive manufacturing; Wire arc additive manufacturing; Interlayer dwelling; Hardness; Microstructure